2016
DOI: 10.1016/j.bbrep.2016.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Monosialoganglioside-GM1 triggers binding of the amyloid-protein salmon calcitonin to a Langmuir membrane model mimicking the occurrence of lipid-rafts

Abstract: GM1 ganglioside is known to be involved in the amyloid-associated diseases and it is a crucial factor for the assembly of amyloid proteins on lipid-rafts, which are lipid structures located on the synaptic plasma membranes. Due to its slow aggregation rate, we employed salmon calcitonin (sCT) as a suitable probe representative of amyloid proteins, to study the interaction between this class of proteins and a membrane model. Here, we prepared a neuronal membrane model by depositing onto mica two Langmuir-Blodge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 71 publications
2
15
0
Order By: Relevance
“…Working with cell lines we found that the neurotoxicity of aggregated and unfractionated sCT samples was similar if not greater than that of Aβ and correlated to the abundance of "lipid-rafts" in the cells [46]. Thus, to investigate this outcome we performed biophysical studies on the interaction of sCT with model membranes mimicking the presence of "lipid-rafts" confirming the GM1 pivotal role [47]. Recently, we fractionated the sCT aggregates and demonstrated that PFOs was the species able to induce neurotoxicity in primary hippocampal neurons and mouse brain slices [5,20].…”
Section: Introductionmentioning
confidence: 94%
“…Working with cell lines we found that the neurotoxicity of aggregated and unfractionated sCT samples was similar if not greater than that of Aβ and correlated to the abundance of "lipid-rafts" in the cells [46]. Thus, to investigate this outcome we performed biophysical studies on the interaction of sCT with model membranes mimicking the presence of "lipid-rafts" confirming the GM1 pivotal role [47]. Recently, we fractionated the sCT aggregates and demonstrated that PFOs was the species able to induce neurotoxicity in primary hippocampal neurons and mouse brain slices [5,20].…”
Section: Introductionmentioning
confidence: 94%
“…Although very simplified compared to the complexity of biological cell membranes, lipid bilayers and monolayers can be employed as useful models. The biomembrane models permitted to investigate the nature of the interaction between phospholipids and drugs or compounds with biological activity . The l ‐α‐dimyristoylphosphatidylcholine (DMPC) is a saturated phospholipid that is found in high quantities as component of healthy and tumour cell membranes of mammalian.…”
Section: Introductionmentioning
confidence: 99%
“…The procedure for the formation of liposomes is relativity simple and allows to use phospholipids of several types as biomembrane models. Moreover, this method is trustworthy in revealing details of the diverse types of interactions of drugs, prodrugs and biologically active substances of different polarity with diverse phases of MLV; therefore, offering information about the miscibility and distribution of the compounds analysed over the phospholipid structures …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations